2019
DOI: 10.1055/a-0916-8916
|View full text |Cite
|
Sign up to set email alerts
|

Analyse der Notfallpatienten einer Universitäts-HNO-Notfallambulanz

Abstract: Zusammenfassung Hintergrund Patientenzahlen in Notaufnahmen nehmen in den letzten Jahren kontinuierlich zu. Das Aufsuchen der Notfallambulanz einer Klinik sagt jedoch nichts über die wahre Dringlichkeit der Behandlung aus. Ziel war es, das Patientenaufkommen der Notfallambulanz einer Universitäts-HNO-Klinik zu analysieren. Methoden Alle Patienten, die sich 2014 als Notfall in einer HNO-Universitätsklinik vorstellten, wurden hinsichtlich demographische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…Some interesting gender differences were found among studies implemented in Europe and India. Studies from Germany [15] and Spain [16] reported that female and male patients were almost equally included in both studies, likewise with the study onwards. However, two studies from India showed a male gender prevalence among care seekers, despite the different setting, with an urban [17] and rural [18] participant enrollment.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Some interesting gender differences were found among studies implemented in Europe and India. Studies from Germany [15] and Spain [16] reported that female and male patients were almost equally included in both studies, likewise with the study onwards. However, two studies from India showed a male gender prevalence among care seekers, despite the different setting, with an urban [17] and rural [18] participant enrollment.…”
Section: Discussionsupporting
confidence: 69%
“…It is not clear whether that difference occurred due to cultural, geographical, or other variables, but it should be taken into account when studying ENT cases attending EDs. Epistaxis was at the top three of the most common reasons of attendance in EDs, in all the aforementioned studies [ 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eine Analyse der HNO-Notfallpatienten in einer deutschen Universitätsklinik ergab folgende häufigsten Diagnosen [2]: ▪ Epistaxis, ▪ Cerumen obturans, ▪ Tinnitus aurium, ▪ Otitis externa ▪ Otitis media.…”
unclassified